Analysis the Effect of Interest Rates and Rupiah Exchange Rate on Indonesian Economic Growth and Business Profit of PT. Pegadaian, Surabaya Area 1 Regional Office - Galuh Candra Wandika; Mukhammad Mabrur Alifiawan; Fahmi Syarief; Chamariyah, Chamariyah (Sean Institute, 2025)
In the world of economics, global conditions have a significant influence with the emergence of inflation or monetary crisis phenomena. This study aims to analyze the effect of interest rates and the rupiah exchange rate on Indonesia's economic growth and operating profit at PT. Pegadaian Regional Office Area Surabaya 1. Using the multiple linear regression method, this study analyzes data on interest rates, the rupiah exchange rate, and Indonesia's economic growth, as well as operating profit data from PT. Pegadaian Regional Office Area Surabaya 1 for the last 5 years, from 2019 to 2023, taken from 12 branch offices. The results of the study indicate that interest rates have a significant negative effect on economic growth, while the rupiah exchange rate has a significant positive effect on economic growth. Meanwhile, in the results of scheme 2, namely the effect of interest rates on operating profit, no significant effect was found, as was the effect of the rupiah exchange rate on operating profit. In addition, this study also provides practical implications for companies to be able to adjust their business strategies in dealing with fluctuations in interest rates and exchange rates in order to maximize operating profits.